Rousseau and the concept of popular sovereignty - Zenkert, Georg (2000)
This essay examines Rousseau's political philosophy from the view point of power. The social contractis not under the modern primacy of "govemment". It rather sees the constitution of community as an autonomous form of power that, under democratic conditions, reaches its realization in popular sovereignty. The legislator's enigmatic figure manifests, although with restriction, a third form of power: authority or the power of action as a competence of political initiatives. The balance among these three forms of power constitutes the framework of the modern conception of politics.